Pengabdian Kampus Mengajar 6: Implementasi Asistensi Mengajar di SDN Kapasan III/145 Surabaya - Yessi Rachmawati; Ni Made Ida Pratiwi (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
Teaching Assistance is one of the student work programs at Teaching Campus 6 at SDN Kapasan III/145 Surabaya. This activity received full support from the school. This program is the result of collaboration between local elementary school teachers and students, with the aim of students replacing the teacher if the teacher is unable to attend to help with the teaching process. Apart from that, students also have a responsibility to improve literacy and hone students' thinking skills. The learning provided adapts to existing learning subjects but is packaged in fun learning with games or ice breaking included. The implementation of Teaching Assistance uses the observation method by observing objects directly during the Teaching Campus 6 assignment period at SDN Kapasan III/145 Surabaya. The results of this activity can show that the role of students in Teaching Assistance plays a very important role in supporting students to increase their motivation to learn and helping teachers carry out their duties.